Year book of agricultural co-operation 1976 - The Plunket Foundation for Co-operative Studies (London : The Plunket Foundation for Co-operative Studies; The Intrenational Cooperative Alliance, 1976)
This book examines the agricultural co-operatives in the rural areas. it also talks about the role of government visa-a-vis co-operative
Includes bibliographical references and index.
mf 22/01/2019
Loans
Keywords: Agriculture, Cooperative